Public Stocks and Rice Supply in COVID-19 Pandemic: Responsibilities and Performance of Brazilian State in Guaranteeing the Human Right to Adequate Food (HRAF) - Gomes Siqueira de Oliveira, Jessica (2023)
Access to food is one of the premises of a nation’s development. In Brazil, a country marked by social inequality and poverty, there was a serious threat to the Human Right to Adequate Food (HRAF), especially during the COVID-19 health crisis. The HRAF, established by the United Nations (UN), guides state actions of signatory countries such as Brazil and makes it enforceable. Thus, the objective of this study was to investigate the state’s role in guaranteeing the supply and regulating rice prices, via the Minimum Price Guarantee Policy during pandemic period. To achieve this aim, data on public and private stocks from the National Supply Company (CONAB) and the Brazilian Institute of Geography and Statistics (IBGE) were obtained and analyzed, to evaluate the management of rice supply mechanisms. It was found that state management was deficient, as the amount of rice stored in public stocks proved to be insufficient in relation to national production, not meeting intervention conditions to guarantee food security for its population. Considering this perspective, it was concluded that public machinery was not anticipated in order to avoid the shortage of a basic product such as rice, which points to a failure of the State to promote food security and guarantee the HRAF.